Analysis of the association between isokinetic knee strength with offensive and defensive jumping capacity in high-level female volleyball athletes - Sattler, T.; Sekulic, D.; Esco, M. R.; Mahmutovic, I.; Hadzic, V. (Journal of Science and Medicine in Sport, 2015)
Objectives: Isokinetic-knee-strength was hypothesized to be an important factor related to jumping performance. However, studies examining this relation among elite female athletes and sport-specific jumps are lacking. This investigation determined the influence of isokinetic-knee flexor/extensor strength measures on spike-jump (offensive) and block-jump (defensive) performance among high-level female volleyball players. Design: Cross-sectional laboratory study. Methods: Eighty-two female volleyball athletes (age = 21.3 ± 3.8 years, height = 175.4 ± 6.76 cm, and weight = 68.29 ± 8.53 kg) volunteered to participate in this study. The studied variables included spike-jump and block-jump performance and a set of isokinetic tests to evaluate the eccentric and concentric strength capacities of the knee extensors (quadriceps - Q), and flexors (hamstring - H) for both legs. Both jumping tests showed high intra-session reliability (ICC of 0.87 and 0.95 for spike-jump and block-jump, respectively). The athletes were clustered into three achievement-groups based on their spike-jump and block-jump performances. Results: For the block-jump, ANOVA identified significant differences between achievement-groups for all isokinetic variables except the Right-Q-Eccentric-Strength. When observed for spike-jump, achievement-groups differed significantly in all tests but Right-H-Concentric-Strength. Discriminant canonical analysis showed that the isokinetic-strength variables were more associated with block-jump then spike-jump-performance. The eccentric isokinetic measures were relatively less important determinants of block-jump than for the spike-jump performance. Conclusions: Data support the hypothesis of the importance of isokinetic strength measures for the expression of rapid muscular performance in volleyball. The results point to the necessity of the differential approach in sport training for defensive and offensive duties.